CHI '02 Extended Abstracts on Human Factors in Computing Systems 2002
DOI: 10.1145/506443.506465
|View full text |Cite
|
Sign up to set email alerts
|

'Visual literacy' as challenge to the internationalisation of interfaces

Abstract: Following a social semiotic approach, this paper questions the Western cultural assumptions underpinning the web's evolving navigational conventions, and investigates to what extent a group of South African students command the currently dominant Western conventions. South African students (both novices and experienced web users) completed a series of visual exercises, where they interpreted a set of interface and conceptual conventions in common use on the web. Conceptual questions attempted to address to wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…In South Africa, this claim resonates with the experiences of many of the disadvantaged students at universities and, in the context of this study, 3rd-year students from historically disadvantaged backgrounds whose limited experience of academic literacy presents them with significant pedagogical impediments (Walton et al, 2001). Addressing academic illiteracy in higher education is challenging, particularly when students are expected to understand, interpret, and critically analyse the concept of social entrepreneurship.…”
Section: Using Film As a Form Of Media Literacysupporting
confidence: 58%
See 1 more Smart Citation
“…In South Africa, this claim resonates with the experiences of many of the disadvantaged students at universities and, in the context of this study, 3rd-year students from historically disadvantaged backgrounds whose limited experience of academic literacy presents them with significant pedagogical impediments (Walton et al, 2001). Addressing academic illiteracy in higher education is challenging, particularly when students are expected to understand, interpret, and critically analyse the concept of social entrepreneurship.…”
Section: Using Film As a Form Of Media Literacysupporting
confidence: 58%
“…Students initially acquire a wide range of literacies from early childhood and, depending on their gender, social class, and race, are more or less likely to be prepared for the rigorous tasks and practices of school-based literacy (Walton, Marsden, & Vukovic, 2001). In South Africa, this claim resonates with the experiences of many of the disadvantaged students at universities and, in the context of this study, 3rd-year students from historically disadvantaged backgrounds whose limited experience of academic literacy presents them with significant pedagogical impediments (Walton et al, 2001).…”
Section: Using Film As a Form Of Media Literacymentioning
confidence: 99%
“…Similarly, users also have their own behaviour and mental models on how the user interface should behave. Also, it leads to the users' preferences and readiness to use the mobile learning application [41]. If the mobile learning application is good, the users will be more engaging to use the application.…”
Section: A Students Willingness To Adopt Mobile Learningmentioning
confidence: 99%
“…These technologies have been forged with a first world perspective, and their value (and limitations) for emergent users needs to be understood and appropriated carefully [2]. For example, early work with users in South Africa showed that hierarchical menus-widely used in developed regions-may cause problems in cultures where relationships are understood in a non-hierarchical, "grandmother-mother-daughter," sense [41]. Turning to more sophisticated interactions, where the device learns about the user over time and adjusts the interface or optimises performance: these strategies are challenged in emergent user contexts where sharing of devices is far more common, and the phone is less of a personal technology and more of a communal one [39].…”
Section: Introductionmentioning
confidence: 99%